Green Marketing And Sustainable Development: A Review - Akansha Malviya, (AG Volumes, 2021)
Thirty years ago, environmental issues appeared to affect every global citizen, business, and organisation. According to studies conducted across the world, consumers are becoming more concerned about the environment, and as a result, their behaviour is changing. When we talk about “green marketing”, we're talking about strategies for creating, developing, and disseminating goods and services that meet the requirements of customers while also being environmentally friendly in terms of raw material usage, energy use, and so on. A literature review on “green marketing” intervention methods and sustainable development is conducted in this article, with a focus on green marketing intervention strategies to environmental issues now confronting the global community. A new study shows that green marketing methods help both people and businesses while also protecting the environment for long-term growth. Green marketing's shortcomings and prospects as a field, as well as research directions in the future, are also examined.